Jogo tríptico na formação inicial do professor de ciências: uma proposta de ensino de física sob o enfoque CTS que busca promover ACT - Melo, Marcos Gervanio de Azevedo (2019)
This thesis discusses the construction of the triptych game - a learning object supported by a generative theme, which is based on Paulo Freire, and which is divided into three stages: (i) the controversial music, (ii) the ideological journal and (iii) the mock jury - developed in a process of collaboration and cooperation with undergraduate students of science at the Federal Technological University of Paraná. The theme of the study comes from the need to train the future science teacher as a critical intellectual and to provide reflections on problems of science teaching that make the process of scientific and technological literacy difficult - STL. The study aims to analyze contributions to the promotion of STL, which may arise in the initial formation of the science teacher of the Federal Technological University of Paraná through the construction of the triptych game. It is a phenomenological research of applied nature and with a qualitative approach that uses technical procedures of action research. The collected data are analyzed in order to follow Laurence Bardin Content Analysis guidelines. The study has as target population 28 undergraduate students of the Interdisciplinary Degree in Natural Sciences of the Federal Technological University of Paraná. The research was conducted at the aforementioned university in Ponta Grossa - PR. During eleven meetings, there was a didactic sequence that was divided into: collaborative training activities and planning and construction of triptych game components. The research sought the theoretical support of Paulo Freire, who envisions the teaching formation contemplated by a reflection directed to the educative-progressive practice, favorable to the autonomy of being of the individual. The results showed that the construction of the triptych game provides a more diversified contact with the dimensions of scientific knowledge, valuing attitudes and scientific-investigative skills that represent important attributes of procedural and attitudinal dimensions. The results also showed an appreciation of contemporary knowledge, important to the conceptual dimension, such as Nuclear Physics subjects, which contribute to a current perception of science in Physics teaching. The triptych game presented a rich context of reflection on the epistemological dimension of science, allowing us to understand how science is born and develops and how it can be influenced by external interference; allowed a contact with structuring axes and elements of STL and provided a systematization of actions similar to the sequence of teaching events, which better organizes the materials STS - Science, Technology and Society - pointed out by Aikenhead. Therefore, the triptych game points towards the integral formation of the future science teacher by valuing his criticality and autonomy and providing education as a process of awareness that brings him closer to a critical intellectual and less to an education technician.